Interaction of Levitating Microdroplets with Moist Air Flow in the Contact Line Region; Nanoscale and Microscale Thermophysical Engineering; Vol. 21, iss. 2 - Kabov O. A. Oleg Aleksandrovich; Zaytsev D. V. Dmitry Valerjevich; Kirichenko D. P. Dmitry Pavlovich; Azhaev V. S. Vladimir Sergeevich (2017, 2017)
Title screen